Drying Kinetics and Stabilisation of Sludge in Sludge Lagoon - Ong, Bee Yen (2001)
Sludge lagoon is a simple and cost effective method for sludge dewatering, especially in countries where land is available and relatively inexpensive, and the evaporation rate is higher than the precipitation rate. Immediate or short term solution is required to solve the problem of high sludge production rate in the country. Sludge lagoon holds privileges as various treatment processes can occur simultaneously in the lagoon, which include thickening, dewatering, storage and stabilisation. Two types of sludge lagoons with different initial sludge depth (O.750m and O.375m) were investigated for the drying behaviour and drying efficiency. The first design is sludge lagoon with clay bottom where the dewatering mechanisms are decanting supernatant and evaporation. The second design is sludge lagoon installed with sand and underdrains system, where the dewatering mechanisms are filtration or draining and evaporation. Septic tank sludge was used in this study and the experiment was carried out under transparent roof to avoid raining effects. Sludge drying kinetics models with high fitness (as shown by regression factor, R2 higher than 0.90) had been developed to describe sludge drying behaviour. Drying of sludge in sludge lagoon with clay bottom can be best described by exponential function, whereas, drying of sludge in sludge lagoon with sand and underdrains system followed logarithmic function. The results of the study show that sludge lagoon with sand and underdrains system and shallower sludge depth had highest drying efficiency. Decanting supernatant can remove most of the free water, whereas draining or filtration mechanism can remove all the free water and part of the interstitial (capillary) water. Highest sludge drying rate had contributed towards highest sludge compaction rate. As the drying process proceeded, total solids content and nitrate content were increased, whereas pH value and ammonium content were reduced. The reduction in volatile solids was lower than 4 percent for all sludge lagoons during the study period. Sludge lagoon with highest drying efficiency was associated with highest reduction in fecal coliform density. Generally, concentrations of heavy metals detected in the final sludge were below the acceptable USEPA limits for land application of clean sludge except for lead. Final sludge contained high percentage of primary nutrient values where the possibility for beneficial reuse as soil conditioner should be investigated.